Borohydride method modification in synthesizing nano zero valent iron and its application in DDT removal - Ulucan-Altuntas, Kubra; Debik, Eyup (SPRINGER HEIDELBERG, 2018)
Among the methods used in the literature for the synthesizing of nano zero valent iron (nZVI), borohydride is the most commonly used method; it is seen that different variables are used together. In this study, optimum nano zero valent iron (nZVI) synthesizing method using borohydride method has been modified by using multiple optimization method in terms of both particle size and zeta potential. Selected independent variables are selected as iron sulfate concentration, ethanol ratio, and flow rate of borohydride solution. With the optimum synthesis method determined, the lowest particle size was obtained as 70nm only when the particle size was taken into consideration, whereas 88.2nm nZVI could be produced when both the particle size and the zeta potential were taken into consideration. In addition, the removal of DDT, which is the most commonly used persistent organic pollutant pesticides in the world, was investigated by nZVI synthesized. Different initial DDT concentration was investigated by expressing oxidation reduction potential (ORP) difference, removal rates, and oxidation byproducts. When DDD and DDE concentrations are considered, it is found that DDT is more likely to oxidize in DDD in all studied initial DDT concentrations. Removal rate was higher than 80% with initial concentrations lower than 125g/L, which is a high concentration that could be found in surface waters.
Keywords: nZVI; DDT metabolites; Response surface methodology; Desirability function; Multiple optimization; ENVIRONMENTAL APPLICATIONS; NANOPARTICLES; REMEDIATION; Environmental Sciences & Ecology